2019
DOI: 10.22201/fmvz.24486760e.2019.1.656
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a single application of coumestrol and/or dimethyl sulfoxide, on sex hormone levels and vaginal cytology of anestrus bitches

Abstract: Canine overpopulation continues to be a problem with serious public health implications, despite a diversity of programs and strategies that have been implemented for its control. Coumestrol (COU) is an organic compound with estrogenic activity, thus having the potential to alter reproduction in mammals. COU is commonly dissolved in dimethyl sulfoxide (DMSO) before administration; however, evidence indicates that DMSO is not inert. The aim of this study was to assess the effects of either a single oral adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
1
6
0
1
Order By: Relevance
“…Changes in the ratio of these cells occur due to the action of sex hormones, including estrogen and progesterone. However, it was proposed to count the number of erythrocytes and leukocytes (Antonov, 2017;Arlt, 2018;Mason, 2018;Peña-Corona et al, 2019). In addition, with the help of vaginal cytology, it is possible to determine the pathological condition of the reproductive tract of the dog (Kim et al, 2018;Šiugždaitė et al, 2018;.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in the ratio of these cells occur due to the action of sex hormones, including estrogen and progesterone. However, it was proposed to count the number of erythrocytes and leukocytes (Antonov, 2017;Arlt, 2018;Mason, 2018;Peña-Corona et al, 2019). In addition, with the help of vaginal cytology, it is possible to determine the pathological condition of the reproductive tract of the dog (Kim et al, 2018;Šiugždaitė et al, 2018;.…”
Section: Introductionmentioning
confidence: 99%
“…(11) The canine and feline overpopulation represent a serious problem. (25) The most common strategies for population control are humanitarian euthanasia and surgical spaying and neutering. (26,27) However, Diase et al (28) reported that they do not have a significant impact on the decrease in the animal population since it has even been estimated that with neutering 100 % of the animals annually, it would not be possible to obtain proportions higher than 86 % and 88 % of the dogs and cats neutered respectively after 20 years due to the high introduction of new intact animals, and would only obtain a reduction of 12-14 % of the dog population.…”
Section: Resultsmentioning
confidence: 99%
“…The estrous cycle represents a complex neurohumoral process characterized by morphological and physiological changes in some of the reproductive organs, such as the vagina. These cyto-morphological changes in exfoliated cells in the vaginal smears, fairly reflect the underlying endocrine events of the reproductive cycle, due to sensitivity of vaginal epithelium to stimulation by sex hormones (Kinoshita et al, 2012;Peña-Corona et al, 2019;Holumbiyovska et al, 2021) and are, thus, considered as a better predictor of the breeding time.…”
Section: Introductionmentioning
confidence: 91%